Queijos gorgonzola, prato, parmesão e mussarela: influência do tempo de maturação no perfil de aminas bioativas, aminoácidos livres, textura e características físico-químicas e microbiológicas - Gisela de Magalhães Machado Moreira (2018)
Ripening is an important step in the production of cheeses, since the biochemical transformations that occur in this period are responsible for the characterization of the final product and affects its quality and safety. The objective of this work was to produce Mozzarella, Gorgonzola, Prato and Parmesan cheeses and characterize them during ripening concerning biochemical profiles (free amino acids and bioactive amines), physical-chemical, texture and microbiological aspects. The performance parameters of the method for simultaneous evaluation of 10 bioactive amines, 19 amino acids and the ammonium ion by UHPLC-UV showed that the method is suitable for the determination of these substances in the studied varieties of cheese. The cheeses were in accordance with the specific legislation of fat in dry matter (FDM) and humidity for each variety. Extension and depth of proteolysis indexes increased in all cheeses and in the last analysis time were, respectively, 30.7% and 24.4% at 49 days of Gorgonzola; 13.4% and 7.1% at 85 days of Mussarela; 13.2% and 6.7% at 42 days of the Prato, and 21.6% and 13.5% at 181 days of Parmesan. Parmesan cheese (737 mg/100 g) and Gorgonzola (496 mg/100 g) were the cheeses with the highest overall free amino acid content, at the end of ripening time assessed. The most common amino acids found in all cheeses were lysine, leucine, phenylalanine and glutamic acid, whereas glycine and cystine were the least prevalent. Tyramine was the amine present in all varieties and in greater quantity. The polyamines spermine and spermidine were not found in any cheese and serotonin was present in Gorgonzola and Parmesan. The texture parameters that showed variation during ripening were cohesiveness in Gorgonzola, gumminess and chewiness in Mozzarella, elasticity and adhesiveness in Prato and adhesiveness in Parmesan. Except for Mozzarella, a decrease in viable mesophilic aerobic count during ripening of all cheeses was observed. The lactic acid bacteria count changed only in Parmesan cheese, showing a decrease over time. The approach used for cheese characterization was efficient and the multivariate analysis synthesized the influences that distinguish each variety. The data generated in this work increase the knowledge on the factors that affect the intrinsic characteristics and the quality of some cheeses produced in Brazil. It can be used as an instrument for classification and decision making about improvements in productive processes and possibly in the pertinent legislation, regarding characterization, quality and standardization of products, and also from the point of view of public health.